KAPASITAS PEMERINTAH DESA DALAM MENGELOLA DANA DESA DI DESA DOMPAS KECAMATAN BUKIT BATU KABUPATEN BENGKALIS TAHUN 2015 - Sulistia, Rhara; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Availability of village finances is one of the main components in the implementation of rural development. It is necessary ability of government finances rural villages to manage effectively and efficiently. In supporting the success of development in the village of the central government provides financial assistance directly called by the village fund as it is regulated in Government Regulation No. 60 of 2014 which the village fund is prioritized for rural development and empowerment of rural communities. Village government capacity to manage the funds of this country need to be considered to see that new funds this village was held for the first time in the year 2015. This study aims to determine the capacity of governments to manage funds rural village in the village of Bukit Batu sub-district Dompas Bengkalis year 2015. This study uses qualitative research with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories. From these results, it can be concluded Dompas village government's ability to manage the funds so far only a recipient country budgets and implementing activities. The village government or the media just as responsible actors in using the budget but has not been able to design a government management in managing finances effectively and efficiently village. Policies manage village funds issued by the central government in 2015 as a forum to support the welfare of people in developing Dompas village is more simply done by providing facilities for rural development whose impact is not so perceived by society. It can be said that the village fund as governments are still not optimal and have not been implemented as the purpose of the village fund in Government Regulation No. 60 of 2014 on the village fund.Keywords: capacity, management, and village government.